Analysis of Service Quality and Customer Satisfaction on Repurchase Halal Fashion Products: Study on Akhwat Bone Sewing House Customers - Lukmana, Ayu (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of service quality on repurchasing and the effect of customer satisfaction on repurchasing halal fashion products at the Bone Sewing House (RJA). The variables used are Service Quality (X1), Customer Satisfaction (X2) as the independent variable and Repurchase (Y) as the dependent variable. This study uses a quantitative approach. The research was conducted using a purposive sampling technique, with a sample of 80 respondents. The data collection method was through distributing questionnaires to the customer population of the Bone Sewing House (RJA). The data analysis technique used is Partial Least Square (PLS). The results of this study indicate that service quality (X1) has a significant effect on repurchase (Y) and customer satisfaction (X2) has a significant effect on repurchase (Y) with a sig value of 0.000, which means the value is less than α 0.05 or (0.000 < 0.05).